Tombs of the South Asasif necropolis : new discoveries and research 2012-2014 ; Vol. 2 - Pischikova, Elena; Pischikova, Elena (The American University in Cairo Press, 2018)
This volume is the second joint publication of the members of the American-Egyptian archaeological team South Asasif Conservation Project, working under the auspices of the Ministry of State for Antiquities and directed by the editor. The Project is dedicated to the clearing, restoration, and reconstruction of the tombs of Karabasken (TT 391) and Karakhamun (TT 223) of the Twenty-fifth Dynasty, and the tomb of Irtieru (TT 390) of the Twenty-sixth Dynasty, on the West Bank of Luxor. This volume will cover the next three seasons of the work of the Project from 2012 to 2014